Regulation and control of the use of Cannabis and Cannabidiol in "novel foods" - Dobrina Tsvetkova; Lily Peykova; Lily Andonova-Dimitrova; Ivanka Pencheva (Pensoft Publishers, 2023)
Cannabis sativa L. is a medicinal plant from family Cannabaceae with many pharmacological activities. The recent appearance of a number of cannabis products in the pharmaceutical market has led to increased requirements for regulation and quality control. The control of Cannabis sativa L. is subject to the Psychotropic Substances Convention, which includes the addictive psychoactive delta-9-tetrahydrocannabinol (THC), and to the Narcotic Drugs Convention, which includes the illicit products: herbal and liquid cannabis, resin, extracts and tinctures of flowering or fruiting tops containing THC. Approved by the FDA for use in chemotherapy are Marinol caps. (THC) and Cesamet caps., containing the synthetic THC-derivative Nabilon. There is no harmonized European Union legislation on the use of cannabis and Cannabidiol (CBD), which antagonizes the THC-psychotropic effect. Legitimate products include seeds, oil, extracts, and seed tinctures of the industrial cannabis chemotype, containing primarily Cannabidiol and less than 0.2% THC. Sativex oral spray (THC/CBD = 1:1) is approved for muscle spasticity in multiple sclerosis. Cannabidiol was not used as a food ingredient in the European Union before 15.05.1997 and is a "novel food" according to Regulation 2015/2283. Flour; protein powder and cannabis seed oil are not "novel foods". Cannabidiol as Epidiolex is FDA approved for epilepsy forms Lennox-Gastaut and Dravet.